Cyanobacteria from bromeliad phytotelmata: new records, morphological diversity, and ecological aspects from northeastern Brazil - Peixoto Ramos, Geraldo Jose; Zanini Branco, Luis Henrique [UNESP]; Do Nascimento Moura, Carlos Wallace (Gebruder Borntraeger, 2019)
Studies on cyanobacterial diversity in bromeliad phytotelmata are scarce, despite their ecological importance in this environment, including N-2 fixation for bromeliad nutrition. Here we discuss the morphological and ecological aspects of 18 cyanobacteria species collected in tank bromeliads in Bahia State, northeastern Brazil. The material examined from 85 sampling units were collected in the phytotelmata of three species of bromeliads. Three morphospecies, Pseudanabaena acicularis, Romeria okensis, and Cyanobium eximium, are reported here for the first time from South America. This study expands our knowledge of cyanobacteria in bromeliad phytotelmata and provides new information on their communities, including the environmental characteristics where each species was found.
Keywords: biodiversity; Bromeliaceae; ecology; morphology; microflora; phytotelm